Mal: Instrument to evaluate the paretic upper limb - Diz, Elisabete (2014)
Neurological disorders resulting from CVA cause, in most cases, hemiplegia which affect significantly the satisfaction of a significant number of activities of daily living. In this regard the evaluation of the quantity and quality of motor function of the upper limbs is important for better planning of rehabilitation programs To analyze the relationship between the affected side after the CVA, the time of occurrence of AVC and handgrip strength to the quantity and quality of use of the paretic upper limb A cross-sectional descriptive study with a quantitative approach nature was given continuation in a non-probabilistic sample of patients who have had a CVA. The instruments of data collection used were the scale Motor Activity Log, a questionnaire to evaluate sociodemographic and clinical variables and handgrip dynamometer to measure grip strength. Of the 148 patients in the sample, 58.8% were males, the average age is 66.12 years (SD = 11.39). The CVA occurred for an average time 35.15 months ago (SD = 28.92), 48% of patients studied remained with the dominant side affected. A correlation between the subscales and handgrip strength on the affected side was found (CCS = 0.290, p = 0.000 for the qualitative and CCS = 0,291 average, p = 0.000 for the quantitative average. Through T test, a difference in the mean of both subscales depending on the affected side may not be the dominant was verified. The results reinforce the importance of studying strength and mobility of the upper limbs, the MAL constitute a useful tool for evaluating the motor performance of the paretic upper limb in patients who have suffered a CVA.